2015
DOI: 10.1007/s12282-015-0593-z
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled study evaluating safety and efficacy of leuprorelin acetate every-3-months depot for 2 versus 3 or more years with tamoxifen for 5 years as adjuvant treatment in premenopausal patients with endocrine-responsive breast cancer

Abstract: BackgroundLuteinizing hormone-releasing hormone (LH-RH) agonists provide effective adjuvant treatment for premenopausal women with endocrine-responsive breast cancer. Here, we investigated appropriate treatment durations of an LH-RH agonist, leuprorelin.MethodsWe conducted an open-label, randomized controlled pilot study to evaluate the safety and efficacy of leuprorelin subcutaneously administered every-3-months for 2 versus 3 or more, up to 5 years, together with daily tamoxifen for 5 years in premenopausal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 21 publications
1
23
0
Order By: Relevance
“…In the current study, patients who chose GnRHa+T treatment received GnRH agonist for 2 years. Shiba et al [17] reported that adjuvant leuprorelin treatment for 3 or more years with tamoxifen showed a survival benefit and safety profile similar to that for 2 years in premenopausal patients with endocrine-responsive breast cancer in a randomized controlled study. Similar to our results, several trials using GnRH agonists for 2 years reported no differences in treatment outcomes between GnRH agonists and chemotherapy [6,13,16,18].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, patients who chose GnRHa+T treatment received GnRH agonist for 2 years. Shiba et al [17] reported that adjuvant leuprorelin treatment for 3 or more years with tamoxifen showed a survival benefit and safety profile similar to that for 2 years in premenopausal patients with endocrine-responsive breast cancer in a randomized controlled study. Similar to our results, several trials using GnRH agonists for 2 years reported no differences in treatment outcomes between GnRH agonists and chemotherapy [6,13,16,18].…”
Section: Discussionmentioning
confidence: 99%
“…23,30 Aromatase inhibitors come with their own set of concerns, including changes in lipid profiles that are generally considered to be small and the clinical significance is unclear. In some trials, aromatase inhibitors seem to offer more safety with regards to thrombosis, but there may be a trade off in terms of lack of cardiovascular protection offered by tamoxifen, like estrogen’s cardiovascular protective effect (outside the thrombotic effects).…”
Section: Discussionmentioning
confidence: 99%
“…4) [23]. It is well recognized that serum E 2 level suppression with an LH–RH agonist can cause BMD reduction, which can be prevented or mitigated with the concomitant use of anti-osteoporosis drugs [24].…”
Section: Discussionmentioning
confidence: 99%